Gender-related cardiac dimension differences between female and male professional soccer players - Sansonio de Morais, A.; Ferreira, G. A.; Lima-Silva, A. E.; Gomes Filho, A. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of this study was to determine if cardiac hypertrophy differs between professional female and male soccer players. METHODS: Twenty-two female and 20 male professional soccer players, and their respective non-athlete controls (22 females and 19 males) were submitted to an echocardiogram. RESULTS: Females had a shorter left ventricular intracavitary diameter and wall thicknesses than males in both groups. However, these differences disappeared when cardiac dimensions were expressed relative to body mass area (P>0.05). Compared to their respective controls, female and male soccer players had a longer (P<0.05) left ventricular end-systolic diameter (female: 1.87±0.16 vs. 1.77±0.15 cm/m2 and male: 1.83±0.21 vs. 1.73±0.16 cm/m2), left ventricular end-diastolic diameter (female: 2.86±0.25 vs. 2.74±0.22 cm/m2 and male: 2.81±0.26 vs. 2.55±0.66 cm/m2), left ventricular posterior wall thickness (female: 0.44±0.06 vs. 0.39±0.04 cm/m2 and male: 0.43±0.04 vs. 0.39±0.10 cm/m2), left ventricular septal wall thickness (female: 0.47±0.06 vs. 0.41±0.04 cm/m2 and male: 0.45±0.04 vs. 0.40±0.11 cm/m2), and left ventricular mass index (female: 91.8±22.1 vs. 72.3±10.5 g/m2 and male: 121.7±20.3 vs. 99.8±13.8 g/m2 ). CONCLUSIONS: Part of the gender differences in cardiac dimensions might be attributed to differences in body dimension. Soccer training increases cardiac dimensions even with BSA correction and females seem to have similar left ventricle remodeling compared to males.